Diacid high-barrier nylon resin as well as preparation method and application thereof
By using a new diacid with a large planar structure and high reactivity to melt polycondensation with aliphatic diamine, the problem of insufficient performance of existing barrier nylon materials was solved, and a high barrier nylon resin suitable for high temperature and high pressure environments was prepared, and the possibility of industrial production was realized.
Patent Information
- Application Number
- CN202510126841.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-27
AI Technical Summary
The existing barrier nylon materials have problems such as poor mechanical strength, low heat resistance grade, and limited color of products, which are difficult to meet the needs of high barrier performance and industrial production.
A new diacid with large planar structure, high reaction activity and excellent thermal stability was prepared by Suzuki-Miyaura reaction, combined with aliphatic diamine for melt polycondensation, and high barrier nylon resin was prepared.
The prepared high-barrier nylon resin exhibits excellent heat resistance, barrier properties and mechanical properties, is suitable for high-temperature and high-pressure environments, and is simple in process and suitable for industrial continuous production.
Smart Images

Figure CN119874602A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a diacid, a nylon resin, a preparation method and an application thereof, and in particular to a diacid, a high-barrier nylon resin, a preparation method and an application thereof. Background Art
[0002] Polymer barrier materials play an increasingly important role in the packaging field due to their advantages such as light weight, non-fragile, corrosion resistance, and easy processing. Therefore, with the widespread application of barrier packaging materials, the demand for barrier materials is increasing, and the research on various polymer barrier materials has attracted increasing attention. In recent years, improving the barrier properties of polymer materials without losing the thermal, mechanical and other properties of the materials has become a hot research direction.
[0003] Polyamide, commonly known as nylon, is a general term for resins containing repeated amide groups on the molecular chain. It is mainly formed by the polycondensation of lactam, amino acid or nylon salt (prepared by the salt-forming reaction of dibasic acid and diamine). Nylon is a type of thermoplastic resin with excellent comprehensive performance. It has the largest output, the most varieties and the widest application among the five major general-purpose engineering plastics. After more than 70 years of development, the application of nylon has expanded from spinning fibers to film packaging, engineering plastics and other fields. Because nylon has a strong polar amide group on the main chain, it is easy to form hydrogen bonds, which increases the intermolecular force and shows good gas barrier properties, chemical stability and solvent resistance. As a common barrier material, nylon can be widely used in automobile plastic fuel tanks and barrier packaging materials due to its performance advantages; but the water affinity of the amide group is very strong, resulting in poor moisture barrier properties of nylon. Changes in environmental humidity will significantly affect the barrier properties and dimensional stability of nylon products.
[0004] CN103160119A discloses a cast nylon nano barrier material, which is made of the following components by weight: 770-947 parts of caprolactam, 1-10 parts of catalyst, 1-10 parts of activator, 50-150 parts of nylon 66, 1-100 parts of inorganic nano oxide and 0-10 parts of other additives. The nylon nano barrier material has the characteristics of high barrier, high strength, high toughness, etc., and has very broad application prospects in the fields of automobile fuel tanks, high barrier plastic bottles, battery separators, oil pipelines, packaging materials, etc. However, since the inorganic nano oxide added to the nylon nano barrier material is basically spherical, its barrier effect on gas or water molecules is inferior to that of layered or flaky inorganic nano fillers; and it has not been surface modified, and the dispersion effect in the caprolactam matrix is poor, which affects the barrier and mechanical properties of the final product.
[0005] CN113881221A discloses a high barrier nylon blend material, comprising the following components by weight: 60-100 parts of nylon resin, 10-30 parts of ethylene-vinyl alcohol copolymer, 10-20 parts of montmorillonite, 1-5 parts of antibacterial agent, and 1-3 parts of dispersant, and the high barrier nylon blend material has high barrier and antibacterial properties. However, the nylon resin selected is long carbon chain nylon 11, which has a low upper limit temperature and is not suitable for special places with strict temperature requirements.
[0006] CN106009640A discloses a high-barrier graphene oxide / nylon nanocomposite material and a preparation method thereof. The barrier properties and mechanical strength of the composite material are improved to a certain extent, but the grafting rate is low, resulting in only a slight improvement in the barrier properties of the material, and only black nylon products can be produced.
[0007] In summary, the currently reported preparation methods of barrier nylon mainly focus on composite modification, and there are fewer cases of copolymerization modification. The obtained barrier nylon has more or less a series of problems such as poor mechanical strength, low heat resistance, and limited product color.
[0008] Therefore, it is urgent to find a diacid with a large planar structure, high reaction activity and excellent thermal stability, and to use it to polymerize to obtain a high-barrier nylon resin with diversified products, excellent mechanical properties, heat resistance and gas barrier properties and applications, as well as a preparation method of diacid and high-barrier nylon resin with a simple production process suitable for industrial continuous production. Summary of the invention
[0009] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a diacid with a large planar structure, high reaction activity and excellent thermal stability.
[0010] The technical problem to be further solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a preparation method of diacid with simple production process and suitable for industrial continuous production.
[0011] A further technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a high-barrier nylon resin and its application with diversified products, excellent mechanical properties, heat resistance and gas barrier properties.
[0012] A further technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a method for preparing high barrier nylon resin with a simple production process and suitable for industrial continuous production.
[0013] The technical solution adopted by the present invention to solve the technical problem is as follows: a diacid, whose molecular structure is: The diacid molecular structure designed by the present invention contains two terminal carboxyl groups and has almost no steric hindrance effect, and will show high reactivity; at the same time, it contains a benzene ring and a carbazole structure, and will show excellent thermal stability compared to a single aliphatic carbon chain structure.
[0014] The technical solution adopted by the present invention to further solve the technical problem is as follows: a method for preparing a diacid, wherein a halogen-substituted carbazole, an organic boron compound, a catalyst and a metal transfer promoter are added to a strong polar solvent, and after reflux reaction, the diacid is filtered and dried. During the reflux reaction, since the reaction temperature is higher than the boiling point of the strong polar solvent, the strong polar solvent boils, and under the condensation of the condenser, a reflux is formed, which accelerates the reaction and prevents the volatilization of the strong polar solvent.
[0015] The inventive concept of the preparation method of the diacid of the present invention is: the method of the present invention uses halogen-substituted carbazole and organic boron compound as raw materials, and obtains a new diacid through Suzuki-Miyaura reaction, which has excellent reaction activity and thermal stability and is suitable for high temperature and high pressure, melt polycondensation reaction process of nylon.
[0016] Preferably, the molar ratio of the halogen-substituted carbazole, the organic boron compound, the catalyst and the metal transfer promoter is 1:2.0-2.2:0.05-0.10:0.8-1.0 (more preferably 1:2.0-2.2:0.05-0.08:0.9-1.0).
[0017] Preferably, the amount of the strong polar solvent used is equivalent to 1.5 to 2.5 times (more preferably 1.8 to 2.4 times) the total mass of the halogen-substituted carbazole, the organic boron compound, the catalyst and the metal transfer promoter.
[0018] Preferably, the temperature of the reflux reaction is 1.05 to 1.10 times the boiling point of the strong polar solvent, and the time is 18 to 30 hours.
[0019] Preferably, the halogen-substituted carbazole includes one or more of 3,6-dichlorocarbazole, 3,6-dibromocarbazole or 3,6-diiodocarbazole.
[0020] Preferably, the organic boron compound includes 4-carboxyphenylboronic acid and the like.
[0021] Preferably, the catalyst includes one or more of tetrakis(triphenylphosphine)palladium, tris(dibenzylideneacetone)dipalladium or bis(triphenylphosphine)palladium dichloride.
[0022] Preferably, the metal transfer promoting agent includes one or more of K3PO4, K2CO3, Na2CO3, KF, Ba(OH)2, potassium tert-butoxide, sodium tert-butoxide or triethylamine.
[0023] Preferably, the highly polar solvent includes one or more of dichloromethane, chloroform, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone.
[0024] The technical solution adopted by the present invention to further solve the technical problem is as follows: a high barrier nylon resin, comprising the diacid structure; its molecular structure is: , wherein a=6, 9, 10, 12 or 14 (more preferably a=6, 9, 10 or 12), b=4, 8, 10 or 12 (more preferably b=4, 8 or 10); the molar ratio of m to n is 10-50:70-190 (more preferably 13-46:86-180). The molecular structure of the high barrier nylon resin of the present invention has structures such as carbazole and benzene ring, which can show excellent heat resistance and barrier properties; dibasic acids and diamines with different carbon chain lengths can be used to adjust the mechanical and processing properties of the high barrier nylon resin. The limitation of a and b is mainly based on whether the corresponding diamine or dibasic acid is easy to obtain or mass-produced industrially, which in turn affects the industrial continuous production of the high barrier nylon resin of the present invention.
[0025] The present invention further solves the technical problem by adopting the following technical solution: A method for preparing a high barrier nylon resin comprises the following steps: (1) adding the diacid and aliphatic diamine into water, stirring to form a salt, and obtaining a component Sx salt solution; adding aliphatic dibasic acid and m-xylylenediamine into water, stirring to form a salt, and obtaining a nylon MXD-y salt solution; (2) The component Sx salt solution and nylon MXD-y salt solution obtained in step (1) are put into a reaction kettle with a catalyst, the air in the reaction kettle is replaced with an inert gas and filled with an inert gas, and then melt polycondensation is carried out, and then the inert gas is filled again and the material is discharged to obtain a high barrier nylon resin.
[0026] The inventive concept of the preparation method of the high-barrier nylon resin of the present invention is: the novel diacid molecular structure contains a rigid, large-planar structure of the carbazole unit, which can reduce the internal rotation freedom of the nylon molecular chain, thereby increasing the packing density of the nylon molecular chain and significantly reducing the free volume inside the polymer. Based on this novel diacid, it is salted with aliphatic diamine to obtain a component Sx solution, and is copolymerized with a nylon MXD-y salt solution to obtain a high-barrier nylon resin with better mechanical properties, heat resistance grade and barrier properties than the barrier nylon resin material currently available on the market obtained by homopolymerization of pure nylon MXD-y salt solution.
[0027] Preferably, in step (1), in the component Sx salt solution, the molar ratio of the diacid to the aliphatic diamine is 0.96 to 1.00: 1. At the ratio, a nylon resin that meets the expected viscosity requirements can be prepared.
[0028] Preferably, in step (1), the amount of water in the component Sx salt solution is 30-40% of the total mass of the diacid and the aliphatic diamine. Water acts as a reaction medium, and a clear and transparent component Sx salt solution can be prepared at the above amount.
[0029] Preferably, in step (1), the aliphatic diamine includes one or more of hexamethylenediamine, nonanediamine, decanediamine, 1,12-diaminododecane or 1,14-diaminotetradecane.
[0030] Preferably, in step (1), in the nylon MXD-y salt solution, the molar ratio of the aliphatic dibasic acid to m-xylylenediamine is 0.96 to 1.00: 1. At the ratio, a nylon resin that meets the expected viscosity requirements can be prepared.
[0031] Preferably, in step (1), the amount of water in the nylon MXD-y salt solution is 30-40% of the total mass of the aliphatic dibasic acid and m-xylylenediamine. Water acts as a reaction medium, and a clear and transparent nylon MXD-y salt solution can be prepared at the amount.
[0032] Preferably, in step (1), the aliphatic dibasic acid includes one or more of adipic acid, sebacic acid, dodecanedioic acid or tetradecanedioic acid.
[0033] Preferably, in step (2), the mass ratio of the component Sx salt solution to the nylon MXD-y salt solution is 1:1 to 6 (more preferably 1:1 to 5).
[0034] Preferably, in step (2), the amount of the catalyst is 0.1-0.5% (more preferably 0.1-0.3%) of the total mass of the component Sx salt solution and the component Sx salt solution. The catalyst, when used in the amount, can catalyze the polycondensation reaction in the positive direction to obtain a high barrier nylon resin with the expected viscosity requirement.
[0035] Preferably, in step (2), the catalyst includes one or more of sodium hypophosphite, potassium hypophosphite or magnesium hypophosphite.
[0036] Preferably, in step (2), the specific process of the melt polycondensation is: firstly carry out a temperature-raising and pressure-maintaining reaction, slowly release the gas and carry out a second temperature-raising and pressure-maintaining reaction, release the gas to normal pressure, discharge the water in the system, and then gradually evacuate the system to carry out a pressure-reducing reaction.
[0037] Preferably, the one temperature-raising and pressure-maintaining reaction refers to: raising the temperature to 210-225°C, maintaining the pressure in the autoclave at 2.0-2.5 MPa, and reacting for 1.5-2.0 hours (more preferably 1.7-2.0 hours). The function of the one temperature-raising and pressure-maintaining reaction is prepolymerization to obtain a low molecular weight high barrier nylon resin prepolymer.
[0038] Preferably, the slow release and secondary temperature and pressure maintenance reaction means: continue to heat to 280-300°C (more preferably 285-300°C), slowly release gas during the heating process to maintain the pressure in the kettle at 1.8-2.0MPa, and react for 1.5-2.0h. The function of the secondary temperature and pressure maintenance reaction is to discharge the water inside the system and slowly increase the molecular weight of the high barrier nylon resin prepolymer.
[0039] Preferably, the stepwise vacuuming for decompression reaction means: first vacuuming to -0.01~-0.03MPa, maintaining pressure reaction for 15~25min, then vacuuming to -0.03~-0.05MPa, maintaining pressure reaction for 15~25min, and finally vacuuming to -0.05~-0.07MPa, maintaining pressure reaction for 12~30min. The vacuum degree of the latter vacuuming is greater than the previous one. Before gradually vacuuming, venting to normal pressure can further discharge the moisture inside the system. The purpose of gradual vacuuming is to further discharge the water generated by the post-condensation reaction, i.e., the decompression reaction process, to promote the reaction in the positive direction, and further increase the molecular weight; the vacuum degree of the early vacuuming is relatively small, in order to avoid the reaction as violent as possible, resulting in the blockage of the vacuum pipe by the extracted moisture and oligomers, and then gradually increase the vacuum degree to extract as much moisture as possible to obtain the nylon resin with the expected molecular weight.
[0040] More preferably, the stepwise vacuuming for reduced pressure reaction means: first vacuuming to -0.01 to -0.02 MPa, then maintaining the pressure for 20 to 25 min, then vacuuming to -0.03 to -0.04 MPa, then maintaining the pressure for 20 to 25 min, and finally vacuuming to -0.05 to -0.06 MPa, then maintaining the pressure for 12 to 24 min.
[0041] Preferably, before the melt polycondensation, the air in the reactor is replaced with an inert gas 3 to 4 times and the inert gas is filled to 0.1 to 0.2 MPa.
[0042] Preferably, after the melt polycondensation, an inert gas is charged to a pressure of 0.2 to 0.3 MPa.
[0043] Preferably, the inert gas includes one or more of carbon dioxide, nitrogen, argon or helium, etc. The inert gas used in the present invention is a high-purity gas with a purity of ≥99.999%.
[0044] The present invention further solves the technical problem by adopting the following technical solution: an application of a high barrier nylon resin, wherein the high barrier nylon resin is used in the technical field of barrier packaging materials.
[0045] The beneficial effects of the present invention are as follows: (1) The diacid of the present invention has a large planar structure, high reactivity, and excellent thermal stability, and is suitable for the high-temperature melt polycondensation reaction requirements of nylon; (2) The relative viscosity of the high barrier nylon resin of the present invention is as high as 2.60, the tensile strength is as high as 119 MPa, the flexural strength is as high as 196 MPa, and the impact strength is as high as 19 kJ / m 2 The melting point is as high as 277.4℃, the initial decomposition temperature is as high as 410.2℃, and the oxygen permeability is as low as 1.2mL / (m 2 ·days), with a water absorption rate as low as 0.13%, suitable for special places with strict requirements on film barrier properties and operating temperature; (3) The high barrier nylon resin of the present invention has diversified products, and the copolymerization ratio of the component Sx salt solution and the nylon MXD-y salt can be flexibly adjusted to produce customized nylon resins with different heat resistance and barrier grades to meet the performance requirements of specific application sites; (4) The method of the present invention has a simple production process and is suitable for industrial continuous production. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 is a time-of-flight mass spectrum of the diacid obtained in Example 1 of the method of the present invention; Figure 2 This is the infrared spectrum of the high barrier nylon resin obtained in Example 1 of the method of the present invention. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with the embodiments and drawings.
[0048] The inert gas used in the examples of the present invention and the comparative examples is a high-purity gas with a purity of ≥99.999%; the raw materials or chemical reagents used in the examples of the present invention, unless otherwise specified, are obtained through conventional commercial channels.
[0049] A diacid embodiment 1 The molecular structural formula of the diacid is: .
[0050] like Figure 1 As shown, there is an obvious characteristic peak of 407.224 m / z in the time-of-flight mass spectrum, corresponding to [M (二酸) +H (氢) ] + The measured molecular weight is consistent with the theoretical value of 407.12 g / mol, indicating that the diacid of the molecular structure is successfully synthesized in Example 1 of the method of the present invention.
[0051] A diacid embodiment 2 The molecular structural formula of the diacid is: .
[0052] After detection, there is an obvious characteristic peak of 407.453m / z in the time-of-flight mass spectrum, corresponding to [M (二酸) +H (氢) ] + The measured molecular weight is consistent with the theoretical value of 407.12 g / mol, indicating that the diacid of the molecular structure is successfully synthesized in Example 2 of the method of the present invention.
[0053] A diacid embodiment 3 The molecular structural formula of the diacid is: .
[0054] After detection, there is an obvious characteristic peak of 407.316m / z in the time-of-flight mass spectrum, corresponding to [M (二酸) +H (氢) ] + The measured molecular weight is consistent with the theoretical value of 407.12 g / mol, indicating that the diacid of the molecular structure is successfully synthesized in Example 3 of the method of the present invention.
[0055] A method for preparing a diacid Example 1 325.0g (1 mol) 3,6-dibromocarbazole, 365.1g (2.2 mol) 4-carboxyphenylboronic acid, 57.8g (0.05 mol) Pd(PPh3)4 and 106.0g (1 mol) Na2CO3 were added to 1707.8g (equivalent to twice the total mass of other raw materials) tetrahydrofuran (boiling point: 66°C), refluxed at 70°C for 24 hours, filtered and dried to obtain the diacid (molecular weight: 407.12g / mol).
[0056] Example 2 of a method for preparing a diacid 325.0g (1 mol) 3,6-dibromocarbazole, 348.5g (2.1 mol) 4-carboxyphenylboronic acid, 42.1g (0.06 mol) PdCl2(PPh3)2 and 101.2g (1 mol) triethylamine were added to 1715.3g (equivalent to 2.1 times the total mass of other raw materials) chloroform (boiling point: 61.2°C), refluxed at 65°C for 24 hours, filtered and dried to obtain the diacid (molecular weight: 407.12g / mol).
[0057] Example 3 of a method for preparing a diacid 419.0 g (1 mol) 3,6-diiodocarbazole, 332.0 g (2.0 mol) 4-carboxyphenylboronic acid, 80.9 g (0.07 mol) Pd(PPh3)4 and 212.3 g (1 mol) K3PO4 were added to 2297.2 g (equivalent to 2.2 times the total mass of other raw materials) N,N-dimethylformamide (boiling point: 153°C), refluxed at 162°C for 18 hours, filtered and dried to obtain the diacid (molecular weight: 407.12 g / mol).
[0058] A high barrier nylon resin embodiment 1 The molecular structure formula of the high barrier nylon resin is: , where a=6, b=4, m=18~20, n=162~180.
[0059] like Figure 2 As shown, 3292.33cm -1 The absorption peak of NH stretching vibration is 2936.32cm -1 and 2861.11cm -1 The absorption peak of CH stretching vibration of methylene is 1627.86 cm -1 The characteristic absorption peak of amide I band is 1539.32 cm -1 The characteristic absorption peak of amide II is 1482.33 cm -1 The characteristic absorption peak of the benzene ring is found, and no characteristic absorption peak of the nylon salt is found, indicating that the high-barrier nylon resin with the molecular structure is successfully synthesized in Example 1 of the method of the present invention.
[0060] A high barrier nylon resin embodiment 2 The molecular structure formula of the high barrier nylon resin is: , where a=9, b=4, m=17~19, n=153~171.
[0061] A high barrier nylon resin embodiment 3 The molecular structure formula of the high barrier nylon resin is: , where a=10, b=4, m=14~16, and n=126~144.
[0062] A high barrier nylon resin embodiment 4 The molecular structure formula of the high barrier nylon resin is: , where a=12, b=4, m=13~16, and n=117~144.
[0063] A high barrier nylon resin embodiment 5 The molecular structure formula of the high barrier nylon resin is: , where a=6, b=8, m=30~33, n=120~132.
[0064] A high barrier nylon resin embodiment 6 The molecular structure formula of the high barrier nylon resin is: , where a=6, b=10, m=37~39, n=111~117.
[0065] A high barrier nylon resin embodiment 7 The molecular structure formula of the high barrier nylon resin is: , where a=6, b=4, m=34~36, n=153~162.
[0066] A high barrier nylon resin embodiment 8 The molecular structure formula of the high barrier nylon resin is: , where a=6, b=4, m=44~46, n=86~90.
[0067] After testing, in the above-mentioned high-barrier nylon resin embodiments 2 to 8, there are obvious absorption peaks of NH stretching vibration, absorption peaks of methylene CH stretching vibration, characteristic absorption peaks of amide I band, characteristic absorption peaks of amide II band and characteristic absorption peaks of benzene ring, which are close to the characteristic peak positions of high-barrier nylon resin embodiment 1, and no characteristic absorption peaks of nylon salt are found, indicating that the high-barrier nylon resins with the above-mentioned molecular structure are successfully synthesized in embodiments 2 to 8 of the method of the present invention.
[0068] A method for preparing high barrier nylon resin Example 1 (1) 399.0 g (0.98 mol) of the diacid obtained in Method Example 1 and 116.2 g (1 mol) of hexamethylenediamine were added to 154.6 g (water / (diacid+aliphatic diamine)=30%, the same below) of water, stirred to form salt, and 669.8 g of component S-6 salt solution was obtained; 1289.0 g (8.82 mol) of adipic acid and 1225.7 g (9 mol) of meta-phenylenediamine were added to 754.4 g (water / (aliphatic dibasic acid+meta-phenylenediamine)=30%, the same below) of water, stirred to form salt, and 3269.1 g of nylon MXD-6 salt solution was obtained; (2) 669.8 g of the component S-6 salt solution obtained in step (1), 3269.1 g of the nylon MXD-6 salt solution and 7.9 g of sodium hypophosphite were added to a reactor. The air in the reactor was replaced with high-purity nitrogen three times and filled with high-purity nitrogen to 0.15 MPa, and then melt polycondensation was carried out: first, the temperature was raised to 210°C, and the pressure in the reactor was maintained at 2.0 MPa. The temperature was raised and the pressure was maintained for 2.0 h. The temperature was continued to be raised to 300°C. During the heating process, the gas was slowly released to maintain the pressure in the reactor at 1.8MPa, and carry out secondary temperature and pressure reaction for 1.5h, then release the air to make the pressure in the reactor return to normal pressure, discharge the water in the system, and use a vacuum pump to gradually evacuate and carry out reduced pressure reaction: first evacuate to -0.02MPa, maintain the pressure for 20min, then evacuate to -0.04MPa, maintain the pressure for 20min, and finally evacuate to -0.06MPa, maintain the pressure for 12min, then fill in high-purity nitrogen to 0.3MPa, release the material, and obtain high barrier nylon resin.
[0069] A method for preparing high barrier nylon resin Example 2 (1) 399.0 g (0.98 mol) of the diacid obtained in Method Example 1 and 158.3 g (1 mol) of nonanediamine were added to 195.1 g (35%) water, stirred to form a salt, and 752.4 g of component S-9 salt solution was obtained; 1302.2 g (8.91 mol) of adipic acid and 1225.7 g (9 mol) of meta-phenylenediamine were added to 884.8 g (35%) water, stirred to form a salt, and 3412.7 g of nylon MXD-6 salt solution was obtained; (2) 752.4 g of the component S-9 salt solution obtained in step (1), 3412.7 g of the nylon MXD-6 salt solution and 10.4 g of sodium hypophosphite were added to a reactor. The air in the reactor was replaced with high-purity nitrogen three times and filled with high-purity nitrogen to 0.15 MPa, and then melt polycondensation was carried out: first, the temperature was raised to 213° C. and the pressure in the reactor was maintained at 2.1 MPa. The temperature was raised and the pressure was maintained for 2.0 h. The temperature was continued to be raised to 295° C. During the heating process, the gas was slowly released to maintain the pressure in the reactor. The pressure was 1.9MPa, and the temperature was raised for a second time to maintain the pressure for 1.5h. The pressure in the reactor was released to normal pressure. After the water in the system was discharged, a vacuum pump was used to gradually evacuate the system for a reduced pressure reaction: first evacuate the system to -0.02MPa, and then maintain the pressure for 20min. Then evacuate the system to -0.04MPa, and then maintain the pressure for 20min. Finally, evacuate the system to -0.06MPa, and then maintain the pressure for 12min. High-purity nitrogen was then introduced to 0.3MPa, and the material was discharged to obtain a high barrier nylon resin.
[0070] A method for preparing high barrier nylon resin Example 3 (1) 399.0 g (0.98 mol) of the diacid obtained in Method Example 1 and 172.3 g (1 mol) of decanediamine were added to 200 g (35%) water, stirred to form a salt, and 771.3 g of component S-10 salt solution was obtained; 1304.8 g (8.93 mol) of adipic acid and 1225.7 g (9 mol) of meta-phenylenediamine were added to 885.7 g (35%) water, stirred to form a salt, and 3416.2 g of nylon MXD-6 salt solution was obtained; (2) 771.3 g of the component S-10 salt solution obtained in step (1), 3416.2 g of the nylon MXD-6 salt solution and 10.8 g of sodium hypophosphite were added to a reactor. The air in the reactor was replaced with high-purity nitrogen three times and filled with high-purity nitrogen to 0.15 MPa, and then melt polycondensation was carried out: first, the temperature was raised to 215°C, and the pressure in the reactor was maintained at 2.2 MPa. The temperature was raised and the pressure was maintained for 2.0 h. The temperature was continued to be raised to 292°C. During the heating process, the gas was slowly released to maintain the pressure in the reactor. The pressure was 1.8MPa, and the temperature was raised for a second time to maintain the pressure for 1.8h. The pressure in the reactor was released to normal pressure. After the water in the system was discharged, a vacuum pump was used to gradually evacuate the system for a reduced pressure reaction: first evacuate to -0.02MPa, and maintain the pressure for 20min, then evacuate to -0.04MPa, and maintain the pressure for 20min, and finally evacuate to -0.06MPa, and maintain the pressure for 12min. High-purity nitrogen was then introduced to 0.3MPa, and the material was discharged to obtain a high barrier nylon resin.
[0071] A method for preparing high barrier nylon resin Example 4 (1) 403.0 g (0.99 mol) of the diacid obtained in method example 2 and 200.4 g (1 mol) of 1,12-diaminododecane were added to 229.3 g (38%) water, stirred to form a salt, and 832.7 g of component S-12 salt solution was obtained; 1289.0 g (8.82 mol) of adipic acid and 1225.7 g (9 mol) of meta-phenylenediamine were added to 955.6 g (38%) water, stirred to form a salt, and 3470.3 g of nylon MXD-6 salt solution was obtained; (2) 832.7 g of the component S-12 salt solution obtained in step (1), 3470.3 g of the nylon MXD-6 salt solution and 11.1 g of potassium hypophosphite were added to a reactor. The air in the reactor was replaced with high-purity nitrogen three times and filled with high-purity nitrogen to 0.15 MPa, and then melt polycondensation was carried out: first, the temperature was raised to 218°C, and the pressure in the reactor was maintained at 2.3 MPa. The temperature was raised and the pressure was maintained for 1.8 hours. The temperature was continued to be raised to 290°C. During the heating process, the gas was slowly released to maintain the pressure in the reactor. The pressure was 1.9MPa, and the temperature was raised for a second time to maintain the pressure for 1.8h. The pressure in the reactor was released to normal pressure. After the water in the system was discharged, a vacuum pump was used to gradually evacuate the system for a reduced pressure reaction: first evacuate to -0.02MPa, and maintain the pressure for 20min, then evacuate to -0.04MPa, and maintain the pressure for 20min, and finally evacuate to -0.06MPa, and maintain the pressure for 18min. High-purity nitrogen was then introduced to 0.3MPa, and the material was discharged to obtain a high barrier nylon resin.
[0072] A method for preparing high barrier nylon resin Example 5 (1) 802.0 g (1.97 mol) of the diacid obtained in Method Example 2 and 232.4 g (2 mol) of hexamethylenediamine were added to 341.4 g (33%) water, stirred to form a salt, and 1375.8 g of component S-6 salt solution was obtained; 1585.6 g (7.84 mol) of sebacic acid and 1089.5 g (8 mol) of meta-phenylenediamine were added to 882.8 g (33%) water, stirred to form a salt, and 3557.9 g of nylon MXD-10 salt solution was obtained; (2) 1375.8 g of the component S-6 salt solution obtained in step (1), 3557.9 g of the nylon MXD-10 salt solution and 13.0 g of potassium hypophosphite were added to a reactor. The air in the reactor was replaced with high-purity nitrogen three times and filled with high-purity nitrogen to 0.15 MPa, and then melt polycondensation was carried out: first, the temperature was raised to 220°C, and the pressure in the reactor was maintained at 2.4 MPa. The temperature was raised and the pressure was maintained for 2.0 h. The temperature was continued to be raised to 292°C. During the heating process, the gas was slowly released to maintain the pressure in the reactor. The pressure is 1.8MPa, and the temperature is increased and the pressure is maintained for a second time for 2.0h. Then, the pressure in the reactor is released to normal pressure. After the water in the system is discharged, a vacuum pump is used to gradually evacuate the system for a reduced pressure reaction: first evacuate the system to -0.02MPa, and maintain the pressure for 20min, then evacuate the system to -0.04MPa, and maintain the pressure for 20min, and finally evacuate the system to -0.06MPa, and maintain the pressure for 24min. Then, high-purity nitrogen is filled in to 0.3MPa, and the material is discharged to obtain a high barrier nylon resin.
[0073] A method for preparing high barrier nylon resin Example 6 (1) 997.5 g (2.45 mol) of the diacid obtained in Method Example 2 and 290.5 g (2.5 mol) of hexamethylenediamine were added to 399.3 g (31%) water, and the mixture was stirred to form a salt, thereby obtaining 1687.3 g of component S-6 salt solution; 1690.5 g (7.35 mol) of dodecanedioic acid and 1021.4 g (7.5 mol) of meta-phenylenediamine were added to 840.7 g (31%) water, and the mixture was stirred to form a salt, thereby obtaining 3552.6 g of nylon MXD-12 salt solution; (2) 1687.3 g of the component S-6 salt solution obtained in step (1), 3552.6 g of the nylon MXD-12 salt solution and 13.4 g of magnesium hypophosphite were added to a reactor. The air in the reactor was replaced with high-purity nitrogen three times and filled with high-purity nitrogen to 0.15 MPa, and then melt polycondensation was carried out: first, the temperature was raised to 223°C, and the pressure in the reactor was maintained at 2.3 MPa. The temperature was raised and the pressure was maintained for 2.0 h. The temperature was continued to be raised to 294°C. During the heating process, the gas was slowly released to maintain the pressure in the reactor. The pressure is 1.9MPa, and the temperature is increased and the pressure is maintained for a second time for 2.0h. Then, the pressure in the reactor is released to normal pressure. After the water in the system is discharged, a vacuum pump is used to gradually evacuate the system for a reduced pressure reaction: first evacuate the system to -0.02MPa, and maintain the pressure for 20min, then evacuate the system to -0.04MPa, and maintain the pressure for 20min, and finally evacuate the system to -0.06MPa, and maintain the pressure for 24min. Then, high-purity nitrogen is filled in to 0.3MPa, and the material is discharged to obtain a high barrier nylon resin.
[0074] A method for preparing high barrier nylon resin Example 7 (1) 798.0 g (1.96 mol) of the diacid obtained in Method Example 3 and 232.4 g (2.00 mol) of hexamethylenediamine were added to 309.1 g (30%) water, stirred to form a salt, and 1339.5 g of component S-6 salt solution was obtained; 1289.0 g (8.82 mol) of adipic acid and 1225.7 g (9 mol) of meta-xylylenediamine were added to 754.4 g (30%) water, stirred to form a salt, and 3269.1 g of nylon MXD-6 salt solution was obtained; (2) 1339.5 g of the component S-6 salt solution obtained in step (1), 3269.1 g of the nylon MXD-6 salt solution and 13.0 g of magnesium hypophosphite were added to a reactor. The air in the reactor was replaced with high-purity nitrogen three times and filled with high-purity nitrogen to 0.15 MPa, and then melt polycondensation was carried out: first, the temperature was raised to 220° C. and the pressure in the reactor was maintained at 2.2 MPa. The temperature was raised and the pressure was maintained for 2.0 h. The temperature was continued to be raised to 296° C. During the heating process, the gas was slowly released to maintain the pressure in the reactor. The pressure was 1.8MPa, and the temperature was raised for a second time to maintain the pressure for 1.8h. Then the pressure in the reactor was released to normal pressure. After the water in the system was discharged, a vacuum pump was used to gradually evacuate the system for a reduced pressure reaction: first evacuate to -0.02MPa, and maintain the pressure for 20min, then evacuate to -0.04MPa, and maintain the pressure for 20min, and finally evacuate to -0.06MPa, and maintain the pressure for 18min. Then high-purity nitrogen was filled in to 0.3MPa, and the material was discharged to obtain a high barrier nylon resin.
[0075] A method for preparing high barrier nylon resin Example 8 (1) 1836.2 g (4.51 mol) of the diacid obtained in Method Example 3 and 534.5 g (4.60 mol) of hexamethylenediamine were added to 711.2 g (30%) water, stirred to form a salt, and 3081.9 g of component S-6 salt solution was obtained; 1289.0 g (8.82 mol) of adipic acid and 1225.7 g (9 mol) of meta-xylylenediamine were added to 754.4 g (30%) water, stirred to form a salt, and 3269.1 g of nylon MXD-6 salt solution was obtained; (2) 3081.9 g of the component S-6 salt solution obtained in step (1) and 3269.1 g of the nylon MXD-6 salt solution and 7.9 g of magnesium hypophosphite were added to a reactor. The air in the reactor was replaced with high-purity nitrogen three times and filled with high-purity nitrogen to 0.15 MPa, and then melt polycondensation was carried out: first, the temperature was raised to 225°C, and the pressure in the reactor was maintained at 2.2 MPa. The temperature was raised and the pressure was maintained for 2.0 h. The temperature was continued to be raised to 300°C. During the heating process, the gas was slowly released to maintain the pressure in the reactor. The pressure was 1.8MPa, and the temperature was raised for a second time to maintain the pressure for 2.0h. Then the pressure in the reactor was released to normal pressure. After the water in the system was discharged, a vacuum pump was used to gradually evacuate the system for a reduced pressure reaction: first evacuate to -0.02MPa, and maintain the pressure for 20min, then evacuate to -0.04MPa, and maintain the pressure for 20min, and finally evacuate to -0.06MPa, and maintain the pressure for 18min. Then high-purity nitrogen was filled in to 0.3MPa, and the material was discharged to obtain a high barrier nylon resin.
[0076] Application Examples 1 to 8 of a High Barrier Nylon Resin The high barrier nylon resin embodiments 1 to 8 are respectively used in the technical field of barrier packaging materials.
[0077] Comparative Example 1 (1) Add 659.1 g (4.51 mol) of adipic acid and 534.5 g (4.60 mol) of hexamethylenediamine to 358.1 g (30%) of water and stir to form a salt to obtain 1551.7 g of nylon 66 salt solution; (2) 1551.7 g of nylon 66 salt solution obtained in step (1) and 1.9 g of sodium hypophosphite are added to a reaction kettle, and the subsequent operation is the same as step (2) of method example 8 to finally obtain nylon 66 resin.
[0078] Comparative Example 2 (1) Add 1289.0 g (8.82 mol) of adipic acid and 1225.7 g (9 mol) of m-xylylenediamine to 754.4 g (30%) of water and stir to form a salt to obtain 3269.1 g of nylon MXD-6 salt solution; (2) 3269.1 g of the nylon MXD6 salt solution obtained in step (1) and 4.1 g of sodium hypophosphite were added to a reaction kettle, and the subsequent operation was the same as step (2) of method example 8 to finally obtain nylon MXD6 resin.
[0079] In order to evaluate the mechanical properties, heat resistance and gas barrier properties of high barrier nylon resin Examples 1 to 8 and Comparative Examples 1 and 2 of the present invention, the tests were carried out according to the following test conditions: Relative viscosity test conditions: The samples of the embodiment and the comparative example were placed in a vacuum drying oven at 120° C. for 4 h, and prepared into a concentrated sulfuric acid solution with a concentration of 0.010 g / mL, and tested using an automatic viscometer in accordance with standard GB / T 38138-2019; Tensile strength test conditions: The tensile specimens were placed in a constant temperature and humidity chamber for 24 hours and tested using a testing machine in accordance with standard GB / T 1040.2-2006; Bending strength test conditions: Place the bending specimen in a constant temperature and humidity chamber for 24 hours and use a testing machine to test according to standard GB / T 9341-2008; Impact strength test conditions: place the impact specimen in a constant temperature and humidity chamber for 24 hours, and use a testing machine to test according to standard GB / T 1043.1-2008; Melting point test conditions: Weigh 5-10 mg of the sample of the embodiment or comparative example, and heat the sample to 300°C for 3 min under the protection of high-purity nitrogen, quench with liquid nitrogen, then heat the quenched sample to 300°C, cool to room temperature, and then heat to 300°C, with a heating rate of 10°C / min, referring to standard GB / T 19466.3-2004; Initial decomposition temperature test conditions: weigh 3-8 mg of the example or comparative example sample, and heat the sample to 700°C under high-purity nitrogen protection. The temperature corresponding to 5% weight loss is the initial decomposition temperature, refer to standard GB / T 33047.1-2016; Oxygen permeability test standard: GB / T 19789 packaging material plastic film and sheet oxygen permeability test coulometer test method is used for testing; Water absorption test conditions: The example or comparative example samples were dried in an oven at 100°C, cooled in the oven, and tested according to ASTM D570-98; The results are shown in Table 1.
[0080] Table 1 Comparison of relevant performance data of high barrier nylon resin examples 1 to 8 of the present invention and comparative examples 1 and 2
[0081] As shown in Table 1, the relative viscosity of high barrier nylon resin embodiments 1 to 8 of the present invention is as high as 2.60, the tensile strength is as high as 119 MPa, the flexural strength is as high as 196 MPa, and the impact strength is as high as 19 kJ / m 2 The melting point is as high as 277.4℃, the initial decomposition temperature is as high as 410.2℃, and the oxygen permeability is as low as 1.2mL / (m 2 ·day), and the water absorption rate is as low as 0.13%, which shows that the high barrier nylon resin embodiments 1 to 8 of the present invention are suitable for special places with strict requirements on film barrier performance and use temperature; compared with the nylon 66 resin obtained in comparative example 1 and the nylon MXD-6 resin obtained in comparative example 2, the high barrier nylon resin embodiment 8 of the present invention can significantly reduce the oxygen permeability and water absorption rate due to the introduction of rigid and large-planar structured carbazole units on its molecular main chain, and with the increase of the carbazole unit content, its barrier performance is further improved, which shows that the introduction of the diacid of the present invention can significantly improve the thermal stability and oxygen barrier property of the obtained polymer.
Claims
1. A diacid, characterized in that Its molecular structure is: .
2. A method for preparing the diacid as claimed in claim 1, characterized in that: Halogen-substituted carbazole, organic boron compound, catalyst and metal transfer promoter are added into a strong polar solvent, refluxed for reaction, filtered and dried to obtain diacid.
3. The method for preparing the diacid according to claim 2, characterized in that: The molar ratio of the halogen-substituted carbazole, the organic boron compound, the catalyst and the metal transfer promoter is 1:2.0-2.2:0.05-0.10:0.8-1.0; the amount of the strong polar solvent is equivalent to 1.5-2.5 times the total mass of the halogen-substituted carbazole, the organic boron compound, the catalyst and the metal transfer promoter; the temperature of the reflux reaction is 1.05-1.10 times the boiling point of the strong polar solvent, and the time is 18-30 hours; the halogen-substituted carbazole includes one of 3,6-dichlorocarbazole, 3,6-dibromocarbazole or 3,6-diiodocarbazole The invention relates to a method for preparing an aqueous solution of at least one of the following materials: the organic boron compound comprises 4-carboxyphenylboric acid; the catalyst comprises one or more of tetrakis(triphenylphosphine)palladium, tris(dibenzylideneacetone)dipalladium or di(triphenylphosphine)palladium dichloride; the metal transfer promoting agent comprises one or more of K3PO4, K2CO3, Na2CO3, KF, Ba(OH)2, potassium tert-butoxide, sodium tert-butoxide or triethylamine; the strong polar solvent comprises one or more of dichloromethane, chloroform, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone.
4. A high barrier nylon resin, characterized in that: Comprising the diacid structure of claim 1; Its molecular structure is: , wherein a=6, 9, 10, 12 or 14, b=4, 8, 10 or 12; the molar ratio of m to n is 10-50:70-190.
5. A method for preparing a high barrier nylon resin as claimed in claim 4, characterized in that: The following steps are involved: (1) Add the diacid and aliphatic diamine described in claim 1 into water, stir to form salt, and obtain a component Sx salt solution; add aliphatic dibasic acid and m-xylylenediamine into water, stir to form salt, and obtain a nylon MXD-y salt solution; (2) The component Sx salt solution and nylon MXD-y salt solution obtained in step (1) are put into a reaction kettle with a catalyst, the air in the reaction kettle is replaced with an inert gas and filled with an inert gas, and then melt polycondensation is carried out, and then the inert gas is filled again and the material is discharged to obtain a high barrier nylon resin.
6. The method for preparing the high barrier nylon resin according to claim 5, characterized in that: In step (1), in the component Sx salt solution, the molar ratio of the diacid to the aliphatic diamine is 0.96-1.00:1; in the component Sx salt solution, the amount of water used is 30-40% of the total mass of the diacid and the aliphatic diamine; the aliphatic diamine includes one or more of hexamethylenediamine, nonanediamine, decanediamine, 1,12-diaminododecane or 1,14-diaminotetradecane; in the nylon MXD-y salt solution, the molar ratio of the aliphatic dibasic acid to meta-phenylenediamine is 0.96-1.00:1; in the nylon MXD-y salt solution, the amount of water used is 30-40% of the total mass of the aliphatic dibasic acid and meta-phenylenediamine; the aliphatic dibasic acid includes one or more of adipic acid, sebacic acid, dodecanedioic acid or tetradecanedioic acid.
7. The method for preparing the high barrier nylon resin according to claim 5 or 6, characterized in that: In step (2), the mass ratio of the component Sx salt solution to the nylon MXD-y salt solution is 1:1-6; the amount of the catalyst is 0.1-0.5% of the total mass of the component Sx salt solution and the component Sx salt solution; the catalyst includes one or more of sodium hypophosphite, potassium hypophosphite or magnesium hypophosphite.
8. The method for preparing the high barrier nylon resin according to any one of claims 5 to 7, characterized in that: In step (2), the specific process of the melt polycondensation is: firstly carry out a temperature-raising and pressure-maintaining reaction, slowly release gas and carry out a second temperature-raising and pressure-maintaining reaction, release gas to normal pressure, discharge water in the system, and then gradually evacuate to carry out a pressure reduction reaction; the first temperature-raising and pressure-maintaining reaction refers to: heating to 210-225°C, and maintaining the pressure in the kettle at 2.0-2.5MPa, and reacting for 1.5-2.0h; the slow release and second temperature-raising and pressure-maintaining reaction refers to: continuing to heat to 280-300°C, slowly releasing gas during the heating process to maintain the pressure in the kettle at 1.8-2.0MPa, and reacting for 1.5-2.0h; the gradual evacuation and pressure-maintaining reaction refers to: continuing to heat to 280-300°C, and slowly releasing gas during the heating process to maintain the pressure in the kettle at 1.8-2.0MPa, and reacting for 1.5-2.0h; The reduced pressure reaction means: first evacuate to -0.01 to -0.03 MPa, then maintain the pressure for 15 to 25 minutes, then evacuate to -0.03 to -0.05 MPa, then maintain the pressure for 15 to 25 minutes, and finally evacuate to -0.05 to -0.07 MPa, then maintain the pressure for 12 to 30 minutes; before the melt polycondensation, replace the air in the reactor with an inert gas 3 to 4 times and fill it with inert gas to 0.1 to 0.2 MPa; after the melt polycondensation, fill it with inert gas to 0.2 to 0.3 MPa; the inert gas includes one or more of carbon dioxide, nitrogen, argon or helium.
9. An application of the high barrier nylon resin as claimed in claim 4, characterized in that: The high barrier nylon resin according to claim 4 is used in the technical field of barrier packaging materials.
Citation Information
Patent Citations
High-barrier nylon blending material
CN113881221A
Polyamide nanometer barrier material and preparation method thereof
CN103160119A
Preparation method of graphene oxide and polyamide nanocomposite material with high barrier property
CN106009640A
Fluorine and polycarbazole containing dianhydride compound and synthesis method thereof
CN112778338A
Preparation method of Cu metal organic framework material and gas separation application
CN116693872A